(untitled) (Progressive Agriculture, 2013)
The study has been conducted to examine the factors influencing farm and nonfarm income of Haor economy in Bangladesh. Dingaputa Haor area of Netrokona district was selected for the present study and a sample of 60 farmers had been taken randomly. The log linear form of Cobb-Douglas production function was chosen to determine the effects of socioeconomic variables on farm income and non-farm income. Apart from this, some descriptive statistical analysis were done to examine the socioeconomic characteristics of sampled households. The estimated results of the regression models revealed that family size and farm size had a significant positive effect on farm income and non-farm income had a significant negative effect on farm income. On the other hand, family size had a positive and significant effect on non-farm income and farm income had a negative and significant effect on non-farm income. To promote the farm and non-farm sector income and strengthening its potential linkages between them, the study mainly recommends increasing efforts on two fronts: first, reforming the institutions responsible for rural development and second, development activities and projects that would enhance farm and non-farm income and the linkages between them. DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16578 Progress. Agric. 23(1 & 2): 143 150, 2012